Knowledge, Attitude, and Practice of Parents of Children with Epilepsy: Knowledge and Practice of Parents of Children with Epilepsy - Kumar, Lalit; Kulsoom, Shazia; Hussain, Wajid (Pakistan Journal of Health Sciences, 2025)
Epilepsy is considered to be present when 2 or more unprovoked seizures occur in a time frame of longer than 24 hours. Objectives: To determine the knowledge, attitude, and practice of parents of children with epilepsy. Methods: This descriptive cross-sectional study was conducted at the Outpatient Department of Pediatric Neurology, National Institute of Child Health, Karachi, Pakistan, from January to June 2025. A total of 262 parents of children aged 1–12 years with epilepsy for ≥6 months were enrolled through non-probability consecutive sampling. A structured 15-item KAP questionnaire (7 knowledge, 5 attitudes, 3 practice) was developed, validated by experts, pilot tested on 20 parents, and showed good reliability (Cronbach’s alpha 0.81). Scores ≥12/15 were classified as good KAP. Analysis was performed using SPSS version 26.0, with chi-square applied post-stratification, taking p<0.05 as significant. Results: In 262 parents, the mean age was 34.6 ± 7.8 years; 117 (44.7%) were fathers, and 145 (55.3%) were mothers. Good knowledge was noted in 209 (79.8%), favorable attitude in 142 (54.2%), and good practice in 122 (46.6%). Overall, a good KAP was observed in 138 (52.7%). Good KAP was associated with urban residence (p=0.006), higher education (p<0.001), and healthcare professionals as information source (p=0.002), but not with gender, age, or income. Conclusions: Most parents had adequate knowledge about epilepsy, while attitudes and practices were comparatively less satisfactory. Better knowledge, attitude, and practice were observed among parents with higher education, those living in urban areas, and those who received information from healthcare professionals.